Immunophilin Deficiency Augments Ca(2+)-Dependent Glutamate Release from Mouse Cortical Astrocytes - Reyes, Reno C. (2010)
Immunophilins are receptors for immunosuppressive drugs such as the macrolides cyclosporin A (CsA) and FK506; correspondingly these immunophilins are referred as cyclophilins and FK506-binding proteins (FKBPs). In particular, CsA targets cyclophilin D (CypD), which can modulate mitochondrial Ca(2+) dynamics. Since mitochondria have been implicated in the regulation of astrocytic cytosolic Ca(2+) (Ca(2+)(cyt)) dynamics and consequential Ca(2+)-dependent exocytotic release of glutamate, we investigated the role of CypD in this process. Cortical astrocytes isolated from CypD deficient mice Ppif (−/−) displayed reduced mechanically-induced Ca(2+)(cyt) increases, even though these cells showed augmented exocytotic release of glutamate, when compared to responses obtained from astrocytes isolated from wild-type mice. Furthermore, acute treatment with CsA to inhibit CypD modulation of mitochondrial Ca(2+) buffering, or with FK506 to inhibit FKBP12 interaction with inositol-trisphosphate receptor of the endoplasmic reticulum, led to similar reductive effects on astrocytic Ca(2+)(cyt) dynamics, but also to an enhanced Ca(2+)-dependent exocytotic release of glutamate in wild-type astrocytes. These findings point to a possible role of immunophilin signal transduction pathways in astrocytic modulation of neuronal activity at the tripartite synapse.